GENERAL ADMINISTRATIVE LAW IN CENTRAL ASIA IN THE DEVELOPMENT PROCESS - Pudelka , Йорг; Deppe , Йенс (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
This article is informative and analytical. The authors considered stages of development of general administrative law in Central Asia. The article will be divided into several parts, each of which will review issues of legislation on administrative procedures in the countries of Central Asia. In this part of the article presents a comparative legal analysis of administrative legislation in Central Asian countries, in particular, administrative procedures and administrative and judicial legislation. There is different classification of the Central Asian countries, depending on the conformity of legislation and law enforcement with the principles of "good governance". The article also presents statistical data on the judicial review of public law disputes. The authors put forward the thesis about the dependence of stable changes in administrative law not only from the formal steps of reform (new laws, new institutions), but also on the genuine changes, innovations, fundamental reforms and changes in awareness of professional law enforcers and society. At the same time legal awareness of citizens appears to be as important as the training and further training of officials, lawyers and judges. There is the principle: "There is no plaintiff without defendant" both in public law and in private. The second part of this article will examine first results of administrative justice reform in the countries of Central Asia, as well as a critical inventory of ongoing reforms and future reforms in the field of administrative law. The authors provide an overview of trends in the development of the law on administrative procedures and administrative procedural law in certain countries of Central Asia.